CLINICAL-ANAMNESTIC AND ECHOCARDIOGRAPHIC MARKERS OF NEONATAL SEPSIS AT DIFFERENT GESTATION AGE OF NEWBORN - Kretsu , Natalia; Koloskova , Olena; Bilous , Tetiana (The Ukrainian Scientific Medical Youth Journal, 2021)
neonatal sepsis remains one of the leading causes of morbidity and mortality in the neonatal age. The involvement of the myocardium in sepsis remains insufficiently studied, in particular in neonatology, where issues of myocardial dysfunction in neonatal generalized infection seem even more controversial, especially in neonatal sepsis at different gestational terms. Objective. To study specific clinical and anamnestic and echocardiographic parameters in infants depending on gestational age for optimization of the prognosis in neonatal sepsis. Material and research methods. To achieve this goal, we observed 57 newborns with a verified diagnosis of "Neonatal sepsis". Group I (23 patients – 40.3%) included newborns with a gestational age of 37-42 weeks, Group II – 34 premature infants (59.7%) with a gestation of up to 36 weeks. The latter group, depending on the gestational age, was divided into IIA subgroup, which was formed by 21 prematurely born patients with NS with a gestational age of 32-36 weeks, and the IIB subgroup – 13 newborns born before 32 weeks of gestation. Research results. The analysis showed that the severity of the impairment in the general condition of the examined newborns general condition was assessed as severe in 47.8% of newborns of group I, in 88.2% of cases in group II (PI: II <0.05), in 85.7% of representatives of subgroup IIA (PI: IIA <0.05) and in 92.3% of children of subgroup IIB (PI: IIB <0.001). It is shown that every third child (30.4%) of group I, 67.6% of newborns of group II (PI: II <0.05), half (52.4%) of the representatives of subgroup IIA (PII: IIA <0.01) and all seriously ill patients (92.3%) of subgroup IIB (PI: IIB, IIA: IIB <0.05) required cardiopulmonary resuscitation in the delivery room. Thus, in relation to full-term patients, the risk of this significant postnatal factor of emergency is likely to increase: for group II: OR - 4.77 (95% CI 2.63-8.68), RR - 2.17 (95% CI 1.57-3.0), AR = 0.37; and for premature babies with a gestational age of less than 32 weeks (IIB subgroup), respectively: OR – 27.44 (95% CI 11.73-64.19), RR – 7.55 (95% CI 5.58-10.21 ), AR – 0.65. The correlation analysis showed that in premature infants suffering from NS, the increase in the functional capacity of the left ventricular myocardium was associated with the female sex (for EF r = 0.94, P = 0.0001, for FS - r = 0, 94, P = 0.0001) and the number of days of inotropic support (for EF r = 0.68, P = 0.043, for FS - r = 0.71, P = 0.03). Conclusions. The analysis of echocardiographic parameters in the group of premature infants revealed a direct correlation between the ejection fraction and cardiovascular resuscitation immediately after birth (r = 0.64) and the duration of inotropic drugs (r = 0.68).